2008
DOI: 10.1038/nchembio.87
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression signatures and small-molecule compounds link a protein kinase to Plasmodium falciparum motility

Abstract: Calcium-dependent protein kinases play a crucial role in intracellular calcium signaling in plants, some algae and protozoa. In Plasmodium falciparum, calcium-dependent protein kinase 1 (PfCDPK1) is expressed during schizogony in the erythrocytic stage as well as in the sporozoite stage. It is coexpressed with genes that encode the parasite motor complex, a cellular component required for parasite invasion of host cells, parasite motility and potentially cytokinesis. A targeted gene-disruption approach demonst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
241
2
3

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 207 publications
(252 citation statements)
references
References 50 publications
5
241
2
3
Order By: Relevance
“…Furthermore, Go 6983, a PKC inhibitor (PfPKB catalytic domain is closely related to PKC) is able to affect in vitro recombinant PfPKB activity and reduce the ability of P. falciparum to invade erythrocytes (Kumar et al, 2004). Consistent with a vital role in parasite development, both PKB and CDPK1 are refractory to gene disruption in P. berghei and P. falciparum (Kato et al, 2008;Solyakov et al, 2011;Tewari et al, 2010). Using a broad-range serine/threonine kinase inhibitor (staurosporine), a marked reduction of phosphorylation of PfGAP45 was observed (Jones et al, 2009).…”
Section: Glideosome: Myosin Motor Assembly and Functionmentioning
confidence: 87%
See 2 more Smart Citations
“…Furthermore, Go 6983, a PKC inhibitor (PfPKB catalytic domain is closely related to PKC) is able to affect in vitro recombinant PfPKB activity and reduce the ability of P. falciparum to invade erythrocytes (Kumar et al, 2004). Consistent with a vital role in parasite development, both PKB and CDPK1 are refractory to gene disruption in P. berghei and P. falciparum (Kato et al, 2008;Solyakov et al, 2011;Tewari et al, 2010). Using a broad-range serine/threonine kinase inhibitor (staurosporine), a marked reduction of phosphorylation of PfGAP45 was observed (Jones et al, 2009).…”
Section: Glideosome: Myosin Motor Assembly and Functionmentioning
confidence: 87%
“…Some of the predicted essential kinases were previously implicated in motility such as cAMPdependent protein kinase A (PKA) (Kurokawa et al, 2011;Leykauf et al, 2010), calcium-dependant protein kinase 1 (CDPK1) (Green et al, 2008;Kato et al, 2008;Winter et al, 2009), protein kinase B (PKB) (Vaid et al, 2008), and protein kinase G (PKG) (Hopp et al, 2012). These datasets therefore constitute an important resource for future hypotheses on the regulation of protein function by phosphorylation and their implications on host cell entry.…”
Section: Phosphoproteomementioning
confidence: 99%
See 1 more Smart Citation
“…GAP45 is known to be phosphorylated by at least two different kinases, CDPK1 and PKB (Green et al, 2008) (Vaid et al, 2008). MTIP is also phosphorylated by CDPK1 (Kato et al, 2008) (Green et al, 2008) and recently it has been shown in T. gondii that dephosphorylation of GAP45 is a prerequisite for its association with MTIP (Gilk et al, 2009). Thus, phosphorylation/dephosphorylation appears to have a role in controlling motor function.…”
Section: -Biological Processes From a Signalling Perspectivementioning
confidence: 99%
“…The best defined function of Ca 2+ as a second messenger come from studies utilizing transgenic parasites expressing a Ca 2+ reporter in P. berghei gametocytes in which cytosolic Ca 2+ mobilization occurs within seconds once cells are exposed to conditions encountered in the mosquito midgut and is critical for the initiation of gametogenesis (Billker et al, 2004 et al, 2004). PfCDPK1 was originally suggested to be exported to the parasitophorous vacuole in a myristoylation/palmitoylation-dependent manner (Moskes et al, 2004) but more recent studies suggest that it is associated with the parasite plasma membrane and has a role in merozoite egress and invasion (Green et al, 2008;Kato et al, 2008 (Green et al, 2008) and PKB phosphorylates GAP45 (Vaid et al, 2008). Clearly, Ca 2+ -dependent pathways need to be dissected to provide insights of molecular mechanisms underlying parasite development.…”
mentioning
confidence: 99%